The Impact of the Integration of Urban and Rural Medical Insurance on Migrant Workers' Overwork: Evidence From China - Xue, Zengxin; Li, Bowei (Frontiers in Public Health, 2022)
In recent years, the problem of migrant workers' excessive labor has attracted much attention. The implementation of the integration policy of urban and rural medical insurance has broken the urban-rural dual division system. While improving migrant workers' health and sense of social integration, can they effectively alleviate their overwork? Based on the panel data of China Labor Dynamics Survey (CLDS) in 2016 and 2018, this paper empirically analyzes the impact of the integration of urban and rural medical insurance on migrant workers' overwork by using the differential difference model (DID). The research shows that the integration of urban and rural medical insurance can significantly alleviate the excessive labor of migrant workers; Heterogeneity analysis shows that, comparing with the new generation, the eastern region, the tertiary industry and low education level migrant workers, it is more obviously that the integration of urban and rural medical insurance alleviates the overwork of the older generation, the central and the western regions, the secondary industry and high education level migrant workers. Path analysis shows that the integration of urban and rural medical insurance will improve the social identity and health level of migrant workers, and then reduce the probability of migrant workers' overwork.